The Religious Campus and Adaptive Behavior: A Study of Overseas Students at the Indonesian University of Education - Adjeng Sisca Alifa Pratiwi; Noviandri Talcha Anjani; Raena Putri Ismayanty; Sri Yuniarti (Universitas Pendidikan Indonesia, 2023)
The research article aims to identify the adaptive behavior of students at the Indonesian University of Education when they are overseas and to find indications of religiosity at the Indonesian University of Education and its influence on students' adaptive behavior. Being abroad brings many changes to students at the Indonesian University of Education, especially the changes within themselves. These changes are a form of student adaptation to new environments and situations. The Indonesian University of Education is also known as a religious campus, where the environment is considered quite Islamic. With that, it is necessary to identify whether there is influence from the religious campus environment on students' adaptive behavior. This study used survey research methods and data collection techniques with mixed questionnaires, a combination of open and closed questionnaires. The target of this research is University of Education students who come from outside the Bandung and Jabodetabek areas. The results of the study show that students' adaptive behavior can be seen in several aspects of the respondents such as time management, language adaptation, social adaptation, adaptation to rules that apply in new environments, and changes in patterns of religious activity.